Avaliação do desempenho ambiental das empresas associadas ao Sindipedras de Soledade-RS - Laimer, Viviane Rossato (2008)
Hereafter, it will be shown a research that has been worked out analyzing twenty-two manufacturing companies related to the -so called- Sindipedras Semi Precious Gem Stones Syndicate- of Soledade City, Rio Grande do Sul State, Brazil. The main research s aim was to evaluate the level of sustainability of the mentioned unionized manufacturing companies -of the previously mentioned city-, considering the environmental aspects involved in the productive process. For this purpose, it was used the method of qualitative exploiting research. After the application of the special form developed for this instance -having as a base the method GAIA (2001) - it became then possible the accomplishment of data-collecting stuff. The manufacturing companies were grouped in four sorts of productive processes, these ones determined by the activities developed by the companies. After an individual examination of each one of them, it was next developed an analysis by group, for a subsequent whole scrutiny of their level of sustainability, which demonstrated that they possess an average level of 54,43 %, this, inferred through the survey aspects that made possible to measure such result. Thereupon, having being observed the sustainable performance of the manufacturing companies, there were arisen proposals and actions spotting the aspects with lesser performance, so that the companies can improve its rates of sustainability